Calculation methods for multicircuit transport network fluid dynamic processes - S. Poveshchenko, Tamara; O. Podryga, Viktoriia; A. Poveshchenko, Yury (International Journal of Engineering and Technology, 2018)
The aim of the work is to create an algorithm for a fast and sufficiently accurate calculation of the parameters of a hydraulic network through which fluid transport is carried out. This type of network is characterized by the presence of a large number of contours, elements for various purposes, and branching. The presence of many contours in the network increases the probability of losing the density of connections, the occurrence of leaks, and accordingly the emergency situation. In paper the construction of a finite-difference scheme and the corresponding calculation algorithm is considered, taking as a basis the model of heat and mass transfer by the flow of a single-phase compressible fluid. The proposed solution method is a generalization of the sweep method to the problems of calculating the heat and mass transfer circuit with an arbitrary number of branching and pipe joints.Â